A noção de linguagem em Descartes: ensaio sobre o conceito de linguagem na filosofia dualista de René Descartes - Cominetti, Geder Paulo Friedrich (2013)
Descartes did not write a philosophy of language. A few quotes about this topic generate many interpretations. Most of the language studies in Descartes produce anachronisms or are originated by comparisons with other conceptions, without being led, primarily, by an analysis of the thought about the Cartesian language concept. However, the topic proved to be productive in speculations about the interaction between the human mind and body, which is very discussed by specialists and aggressively attacked by his opposers. Characterized as a Cartesian dualism essay, this study dares to separate the language in two parts, analyzing singly its material aspect, and then its immaterial aspect. This new approach turns the reader s attention to the importance of the material aspect of the language, substantiating the objectivity of the language in the extended substances. The communication only becomes possible because there is, among two or more men, the extension. This concept is classified as the objective aspect of the language, because it is generally in the area of the sensitive experience, apart from the individual and perceptible thought of the men. Concerning the subjective aspect, each individual has a free will and he can make his own thoughts. Indeed, it is in this way that Descartes conceives the language: having the men as the creator of the words meaning, which are represented and implemented by modification of the extension. In addition, he conceives the linguistics signs as representations of thoughts, as explicitness of the internal events of men. Their speech is the explicitness of their thoughts. Therefore, when looking at a set of graphic symbols that he produced, the individual realizes the movement of his thought. These revelations that the mind uses the body as a help in the searching for the truth, because, in the body, the memory can be used as a notebook of the mind demonstrate that the Cartesian dualistic conception of the language helped Descartes in his work on algebra and in his mathematical and scientific discoveries. In conclusion, it is possible to say that the topic has no end in the next pages, but it opens a new route for researchers devote their efforts to investigate the relations between mind and body. This study dares to be completely original in its approach, in the presented problem, but it does not want to bring the reader more than a deepening, at his limit, interpretation of one of the most commented writers in philosophy in the last three centuries.